2011
DOI: 10.2320/jinstmet.75.372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shot Particle on the Mechanism of Creating a Modified Layer by Atmospheric Controlled IH-FPP Treatment

Abstract: Basic mechanisms of generating a surface modified layer formed by a previously developed atmospheric controlled IH FPP system, consisting of induction heating system and fine particle peening system, were investigated. Three types of specimen treated at 900°C in argon with Cr, Al 2 O 3 and Cu shot particles were prepared. Surface microstructures of the treated commercial grade pure iron were characterized with a scanning electron microscope (SEM), an energy dispersive X ray spectrometer (EDX) and an X ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
(1 reference statement)
0
4
0
1
Order By: Relevance
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…It was previously reported that the shot particle elements transferred onto the surface to be processed are diffused into the substrate during heating. 3) For example, when AIH-FPP treatment using Cr particles is applied to steels, a Cr diffused layer is formed on the surface, which is associated with improved corrosion resistance of the steels. 46) It was also reported that when nitriding is applied to steels with a Cr diffused layer, the nitrided layer formed had higher hardness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we conducted a study on the improvement effect and a series of experiments attempting to elucidate the mechanism underlining the effect of atmospheric-controlled induction heating and ne particle peening (AIH-FPP) [18][19][20][21][22][23][24][25] . For example, it was previously reported that by performing AIH-FPP on carbon steel using Cr particles, the components of the Cr particles were transferred onto the surface to be processed and diffused inside the substrate to form a Cr diffusion layer, whereby the corrosion resistance of the carbon steel was improved 22) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a small amount of oxygen is not evacuated but remains in the chamber. This trace oxygen may form oxides on the surface to be processed, which are likely to inhibit the transfer and diffusion of Cr [20][21][22][23] . In the present study, we rst develop a system that reduces the oxygen concentration in the chamber to the order of ppm, much less than a conventional processing apparatus.…”
Section: Introductionmentioning
confidence: 99%